Challenges and opportunities for NGO-government collaboration in healthcare systems of developing countries - Ali Vafaee Najar; Esmat Pardasi; Mehrdad Salehi; Bahare Boshrouei Shargh; Elaheh Hooshmand (Social Sciences and Humanities Open)
Introduction: Governments worldwide increasingly emphasize collaboration with non-governmental organizations (NGOs) in healthcare. However, research on the challenges faced by NGOs, particularly in low- and middle-income countries, remains limited. This study aims to explore these challenges from the perspectives of healthcare managers and NGO leaders in Iran, a low-middle-income country. Method: A qualitative study was conducted using 54 semi-structured interviews with managers from the governmental healthcare sector and active NGO leaders at the national level between 2023 and 2024. Data were analyzed using the framework analysis method in Atlas.T software. Result: The study identified five key categories of challenges affecting NGO-government collaboration: political issues (e.g., policy instability and leadership changes), operational issues (e.g., inefficiencies in collaboration processes), cultural issues (e.g., mutual distrust between stakeholders), managerial issues (e.g., insufficient support and capacity-building), and communication issues (e.g., weak networks and lack of awareness about NGO roles). Conclusion: This study offers a practical framework for addressing the identified challenges, particularly in developing countries. Specific recommendations include establishing consistent policies to ensure stability, simplifying collaboration procedures, and fostering mutual respect between NGOs and government agencies. These measures can enhance NGO effectiveness, ultimately improving healthcare service delivery and patient outcomes.